INCIDENCE AND RISK FACTORS FOR DRY EYE DISEASE IN A TERTIARY HOSPITAL IN NORTH CENTRAL INDIA - MANOJ, GOVILA; MOHAN, VERMA KAMAL; NEYAZ, HASAN SYED; RAM MILAN, PRASOT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Dry eye disease (DED is a severe tear insufficiency condition that affects millions of people worldwide. Dry eye refers to conditions of the tear film brought on by decreased tear production and/or excessive tear evaporation. The study’s objective was to compile data on the incidence of DED and associated risk factors. Methods: The government hospital of Uttar Pradesh (India) served as the study’s site for this cross-sectional and observational study. Clinical observation and the ocular surface disease index survey were used to assess the aim of the study. Results: Patients were screened in total, 652. The incidence of DED was reported in 267 (40.9%) individuals. There were 130 DED patients (48.7%) above the age of 40, followed by those between the ages of 21 and 40 (47.2%). Both genders were equally impacted, with men (50.2%) and women (49.2%). Out of 267 DED patients, 128 (47.9%) had a desk job with a computer. Among the patients, 57 (21.3%) had mild DED, 74 (27.7%) had moderate DED, and 136 (50.9%) had severe DED. The severe DED also showed independent association between the desk job with a computer (Odds Ratio [OR]; 2.782, 95% confidence interval [CI]: 1.694–4.568, p<0.001), cigarette smoking (OR; 1.849, 95% CI: 1.135–3.014, p=0.014), and use of contact lens (OR; 1.972, 95% CI: 1.206–3.223, p=0.007). Conclusion: The frequency of DED is high in Uttar Pradesh. The illness is particularly prevalent in older people, computer-using desk workers, smokers, and contact lens wearers.